A step towards valid detection and quantification of lung cancer volume in experimental mice with contrast agent-based X-ray microtomography - Bidola, Pidassa; De Souza E Silva, Juliana Martins; Achterhold, Klaus; Munkhbaatar, Enkhtsetseg; Jost, Philipp J.; Meinhardt, Anna-Lena; Taphorn, Kirsten; Zdora, Marie-Christine; Pfeiffer, Franz; Herzen, Julia (Scientific Reports, 2019)
Tumor volume is a parameter used to evaluate the performance of new therapies in lung cancer research. Conventional methods that are used to estimate tumor size in mouse models fail to provide fast and reliable volumetric data for tumors grown non-subcutaneously. Here, we evaluated the use of iodine-staining combined with micro-computed tomography (micro-CT) to estimate the tumor volume of ex vivo tumor-burdened lungs. We obtained fast high spatial resolution three-dimensional information of the lungs, and we demonstrated that iodine-staining highlights tumors and unhealthy tissue. We processed iodine-stained lungs for histopathological analysis with routine hematoxylin and eosin (H&E) staining. We compared the traditional tumor burden estimation performed manually with H&E histological slices with a semi-automated method using micro-CT datasets. In mouse models that develop lung tumors with well precise boundaries, the method that we describe here enables to perform a quick estimation of tumorous tissue volume in micro-CT images. Our method overestimates the tumor burden in tumors surrounded by abnormal tissue, while traditional histopathological analysis underestimates tumor volume. We propose to embed micro-CT imaging to the traditional workflow of tumorous lung analyses in preclinical cancer research as a strategy to obtain a more accurate estimation of the total lung tumor burden.
CRIS-Team Scopus Importer:2023-03-08